2004
DOI: 10.1023/b:biod.0000009973.53531.96
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of BTEX Hydrocarbons: Effect of Soil Inoculation with the Toluene-Growing Fungus Cladophialophora Sp. Strain T1

Abstract: The biodegradation of a mixture of benzene, toluene, ethylbenzene, xylene, (BTEX) and methyl-tert-butyl ether (MTBE) was studied in soil microcosms. Soil inoculation with the toluene-metabolising fungus Cladophialophora sp. strain T1 was evaluated in sterile and non-sterile soil. Induction of biodegradation capacity following BTEX addition was faster in the soil native microflora than in axenic soil cultures of the fungus. Toluene, ethylbenzenes, and the xylenes were metabolized by the fungus but biodegradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 32 publications
0
18
0
2
Order By: Relevance
“…To overcome this problem surfactants have been added to contaminated soils to improve the availability of hydrocarbons. The rate of degradation depends on the microbial population, the type and level of contamination (Boldu-Prenafeta et al, 2004). Another way of increasing the biodegradation efficiency can be improving the aeration; the addition of biogenic elements (phosphorus, nitrogen, potassium) has also been proposed (Liužinas, Jankevičius, 2003;Si-Zhong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem surfactants have been added to contaminated soils to improve the availability of hydrocarbons. The rate of degradation depends on the microbial population, the type and level of contamination (Boldu-Prenafeta et al, 2004). Another way of increasing the biodegradation efficiency can be improving the aeration; the addition of biogenic elements (phosphorus, nitrogen, potassium) has also been proposed (Liužinas, Jankevičius, 2003;Si-Zhong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of this work was to determine how sewage sludge can influence the biodegradation activity of soil contaminated with oil products, as well as to determine what groups of microorganisms influence these processes most. It is known that the efficiency of this process depends on the number of microorganisms present in the soil and their ability to adapt, specificity of their functioning, nutritional substances suitable for growth, composition of pollutants, and physicochemical properties of soil (Iwamoto, Nasu, 2001;Vasudevan, Rajaram, 2001;Boldu-Prenafeta et al, 2004). It was determined earlier that a small amount of metals in the sewage sludge only speeds up the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental Contamination due to rise in Petrochemical Industry has become a matter of serious concern from the last few decades (Prenafeta-Bold´u1, 2004). Waste effluent generated from the petrochemical Industry consists of highly toxic derivatives of organic compounds like benzene, toluene, xylene and other poly aromatic compounds .…”
Section: Introductionmentioning
confidence: 99%
“…The group of microorganisms mostly reported for use as bioremediation agents are bacteria; however, fungal species have also been reported to be able to degrade BTEX compounds for use as carbon and energy sources. Prenafeta-Boldú et al (2004) reported the use of a toluene-metabolising fungus to degrade BTEX compounds under various pH conditions. Alvarez and Vogel (1995) highlighted the ability of indigenous bacteria to degrade BTEX compounds without suffering as much metabolic inhibition as micro-organisms from other sources.…”
mentioning
confidence: 99%